Analisis Pengeluaran Sektor Pariwisata Terhadap Ketimpangan Pendapatan Di Indonesia - Azzahra Endah; Isra Yeni (Universitas Negeri Padang, 2025)
This study aims to analyze the impact of tourism sector expenditure on income inequality in Indonesia. This study uses secondary data from the publication of the Central Statistics Agency (BPS) using the main variables of tourist expenditure and poverty, as well as control variables of economic growth, education, and labor force participation rate, with the dependent variable being income inequality. In this study, a panel data regression analysis tool was used using the random effect model method with cross-section data from 34 provinces in Indonesia and a time series from 2015-2022. The findings show that tourist expenditure has a negative and significant effect on income inequality. However, the contribution is not large to income inequality, so the government needs to increase economic growth by equalizing access to education and eradicating poverty so as to reduce income inequality in Indonesia. Penelitian ini bertujuan untuk menganalisis dampak pengeluaran sektor pariwisata terhadap ketimpangan pendapatan di Indonesia. Penelitian ini menggunakan data sekunder yang berasal dari publikasi Badan Pusat Statisttik (BPS) dengan menggunakan variabel utama pengeluaran wisatwan dan kemiskinan, serta variabel kontrol pertumbuhan ekonomi, pendidikan, dan tingkat partisipasi tenaga kerja, dengan variabel terikat adalah ketimpangan pendapatan. Dalam penelitian ini menggunakan alat analisis regresi data panel menggunakan metode random effect model dengan data cross section 34 provinsi di Indonesia dan time series dari tahun 2015-2022. Temuan menunjukan bahwa pengeluaran wisatawan berpengaruh negatif dan signifikan terhadap ketimpangan pendapatan. Namun, kontribusi yang tidak besar terhadap ketimpangan pendapatan, maka pemerintah perlu peningkatan pertumbuhan ekonomi dengan pemerataan akses pendidikan dan pengetasan kemisinan sehingga mampu mengurangi ketimpangan pendapatan di Indonesia.